Self-efficacy for coping behaviour with cancer: A study on cancer patients at Oncology Clinic, HUSM Kubang Kerian / Nur Atiqqah Ismail - Ismail, Nur Atiqqah (2011)
The aim of this study was to ascertain the coping behavior of cancer patients in their daily life by using Cancer Behaviour Inventory (CBI). The problem of cancer in Malaysia is a growing one. A cross-sectional study was carried out at Oncology Clinic, HUSM, Kubang Kerian, Kelantan. Data were obtained through face-to-face interviews using the translated Malay questionnaire. The respondents were selected based on simple random sampling method. The researcher verbally interviewed respondents in filling the questionnaire. A total of 104 respondents, which are 21 males and 83 females ages from 27 years to 72 years old. Result showed stress management was found to be influencing the maintaining positive attitude of patients’ on self-efficacy for coping with cancer. Moreover, the result showed that there is a significant difference for the gender toward patients’ coping behaviour of cancer. The result also showed that there is no significant difference for the age category and marital status of the patients toward maintaining positive attitude. For the type of cancer and stage of cancer, the result also showed that there is no significant difference on coping behaviour of cancer. In conclusion, the greater the confidence people have in their ability to execute courses of action, such as coping behaviors, the higher the probability of attaining some goal, such as maintaining a desired state of quality of life